Intra-individual comparison of CAIPIRINHA VIBE technique with conventional VIBE sequences in contrast-enhanced MRI of focal liver lesions. Issue 86 (January 2017) - Albrecht, M.H.; Bodelle, B.; Varga-Szemes, A.; Dewes, P.; Bucher, A.M.; Ball, B.D.; De Cecco, C.N.; Schoepf, U.J.; Zhu, X.; Zangos, S.; Gruber-Rouh, T.; Wichmann, J.L.; et al.
Abstract: Purpose: To evaluate the impact of controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA) volume interpolated breath-hold examination (VIBE) magnetic resonance imaging (MRI) technique on image quality, reader confidence, and inter-observer agreement for the assessment of focal liver lesions in comparison with the standard VIBE approach. Material and methods: In this IRB-approved intra-individual comparison study, abdominal arterial and portal-venous contrast-enhanced MRI studies were retrospectively analyzed in 38 patients with malignant liver lesions. Each patient underwent both CAIPIRINHA and conventional VIBE 3 T MRI within 3 months, showing stable disease. Images were evaluated using 5-point rating scales by two blinded radiologists with more than 20 and 5 years of experience in MRI, respectively. Readers scored dignity of liver lesions and assessed which liver segments were affected by malignancy (ranging from 1 = definitely benign/not affected to 5 = definitely malignant/affected by malignancy). Readers also rated overall image quality, sharpness of intrahepatic veins, and diagnostic confidence (ranging from 1 = poor to 5 = excellent). Results: Reviewers achieved a higher inter-observer reliability using CAIPIRINHA when they reported which liver segments were affected by malignancy compared to traditional VIBE series (κ = 0.62 and 0.54, respectively, p < 0.05). Similarly, CAIPIRINHA showed a slightly higher inter-rater agreement for the dignity of focal liver lesions versus the standard VIBE images (κ = 0.50 and 0.49, respectively, p < 0.05). CAIPIRINHA series also scored higher in comparison to standard VIBE sequences (mean scores: image quality, 4.2 and 3.5; sharpness of intrahepatic vessels, 3.8 and 3.2, respectively, p < 0.05) for both reviewers and allowed for higher subjective diagnostic confidence (ratings, 3.8 and 3.2, respectively, p < 0.05). Conclusion: Compared to the standard VIBE approach, CAIPIRINHA VIBE technique provides improved image quality and sharpness of intrahepatic veins, as well as higher diagnostic confidence. Additionally, this technique allows for higher inter-observer agreement when reporting focal liver lesions for both dignity and allocation.